1996
DOI: 10.1093/infdis/174.5.1064
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Diphtheria in Russia, 1985--1994

Abstract: The largest diphtheria outbreak in the developed world since the 1960s began in the Russian federation in 1990. One hundred fifty-six Corynebacterium diphtheriae strains from throughout Russia, selected for temporal and geographic diversity, were assayed by ribotyping and multilocus enzyme electrophoresis (MEE). These tests showed significant genetic diversity within the C. diphtheriae species, and ribotyping and MEE data generally correlated well with epidemiologic data. A distinct clonal group of C. diphther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
72
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 30 publications
1
72
0
Order By: Relevance
“…Ribotyping was carried out as described previously. 13 The A11 strain was unlike any toxigenic or nontoxigenic strain found recently in the USA and was unlike strains frequently isolated from the 1990-1996 diphtheria epidemic in the Russian Federation and the NIS (Fig. 4).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Ribotyping was carried out as described previously. 13 The A11 strain was unlike any toxigenic or nontoxigenic strain found recently in the USA and was unlike strains frequently isolated from the 1990-1996 diphtheria epidemic in the Russian Federation and the NIS (Fig. 4).…”
mentioning
confidence: 79%
“…In fact, the waning immunity of a previously immunized population was considered to be a major factor for the recent diphtheria epidemic in Russia and the New Independent States (NIS) of the former Soviet Union in the early 1990s. 1,4,13,15 Here, we describe the isolation of toxigenic C. diphtheriae from the infected wound of a horse. The isolation of toxigenic C. diphtheriae from a horse reiterates the possibility of horses and other animals serving as reservoirs for C. diphtheriae in the USA and potentially playing a role in the circulation of toxigenic strains.…”
mentioning
confidence: 99%
“…However, the source of the epidemic strains remains unclear (Popovic et al 1996). Molecular characterization by ribotyping and/or random amplification polymorphic DNA (RAPD-PCR) of the Russian C. diphtheriae isolates indicated that a distinct clonal group emerged in Russia in 1990 about the time epidemic began.…”
Section: Epidemic and Endemic C Diphtheriae Strainsmentioning
confidence: 99%
“…Forty-six of the isolates were assayed by multilocus enzyme electrophoresis (MEE) as previously described (17).…”
mentioning
confidence: 99%
“…Previous reports of the excellent correlation between MEE, ribotyping, and epidemiologic data prompted us to use these methods in our study (8,17 (16). Unlike the ET 8 complex, which is associated with the recent epidemic in Russia and the former Soviet Republics (New Independent States) and contains only biotype gravis strains (17), the ET 215 complex contains strains of biotypes gravis, mitis, and belfanti.…”
mentioning
confidence: 99%